The Analysis of Students’ Achievement on Listening Skill Based on Introvert Personality - Aisyah; Harianto II; Marisa, Vera (International Journal of Educational Research Excellence (IJERE), 2024)
This research aims to determine the listening skill on students introvert personality. This research was conducted in class XI IPA 1 MAN 1 Deli Serdang by conducting student personality selection by giving questionnaire to find students with introvert personality. Listening test was given after the student personality selection process is done by presenting 3 videos tests that had difference titles and stories in each test. This type of research was a qualitative descriptive research, where the research was observed as a data collection process then describe and interpret the result of the data had been collected in the form of an explanation. Data was obtained from the selection process of the students personality type with questionnaire found that there are only 15% of students who had introverted personality. The listening test result show that students introvert personality had good listening skill with an average score of 90 and the highest was 95.